Immunology in COPD and the use of combustible cigarettes and heated tobacco products - Justyna Błach; Mateusz Siedliński; Wojciech Sydor (European Journal of Medical Research, 2023)
Abstract Chronic obstructive pulmonary disease (COPD) is one of the most common chronic respiratory diseases, characterised by high morbidity and mortality. COPD is characterised by a progressive decline of lung function caused by chronic inflammatory reactions in the lung tissue due to continual exposure to harmful molecules by inhalation. As prevention plays a very important role in COPD, quitting smoking is the most important factor in reducing the decline in lung function. Unfortunately, many people are unable to break their nicotine addiction. This paper summarises current knowledge about combustible cigarettes (CSs) and alternative tobacco products such as heated tobacco products (HTPs) in COPD. The paper focuses on the immunological aspects of COPD and the influence of tobacco products on lung tissue immunology. There are differences in research results between HTPs and CSs in favour of HTPs. More long-term studies are needed to look at the effects of HTPs, especially in COPD. However, there is no doubt that it would be best for patients to give up their nicotine addiction completely.